2024
DOI: 10.1039/d3ob01711g
|View full text |Cite
|
Sign up to set email alerts
|

[2.2]Paracyclophane-based coumarins: effective organo-photocatalysts for light-induced desulfonylation processes

Jules Brom,
Antoine Maruani,
Serge Turcaud
et al.

Abstract: An unprecedented photocatalytic activity of coumarins derived from [2.2]paracyclophane is disclosed, which allows the reductive photocleavage of various sulfonamides under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The removal of the OMe group in ( S p )- 3a by NaH afforded the N–H product ( S p )- 4a almost in quantitative yield (Scheme b), and its structurally similar molecule is a N , O -chelating ligand in the hydroaminoalkylation reaction . UV–vis absorption spectra revealed that compound 4a can absorb light at 365 nm in CH 2 Cl 2 (Scheme S5), and it was further found that under blacklight-irradiation, 4a can act as an effective photocatalyst to realize the reductive cleavage of sulfonamides of the tosyl amide substrate 7 toward N -benzylbenzamide 8 (Scheme f) . Treatment of ( S p )- 4a with POCl 3 furnished the [2.2]­paracyclophane-fused 1-chloroquinoline product ( S p )- 5a in 83% yield (Scheme c).…”
mentioning
confidence: 99%
“…The removal of the OMe group in ( S p )- 3a by NaH afforded the N–H product ( S p )- 4a almost in quantitative yield (Scheme b), and its structurally similar molecule is a N , O -chelating ligand in the hydroaminoalkylation reaction . UV–vis absorption spectra revealed that compound 4a can absorb light at 365 nm in CH 2 Cl 2 (Scheme S5), and it was further found that under blacklight-irradiation, 4a can act as an effective photocatalyst to realize the reductive cleavage of sulfonamides of the tosyl amide substrate 7 toward N -benzylbenzamide 8 (Scheme f) . Treatment of ( S p )- 4a with POCl 3 furnished the [2.2]­paracyclophane-fused 1-chloroquinoline product ( S p )- 5a in 83% yield (Scheme c).…”
mentioning
confidence: 99%